Prevalence of severe mental illness dual diagnosis among inpatients in a psychiatric hospital / Sughashini Subramaniam - Sughashini , Subramaniam (2019)
The high prevalence of co-morbidity or dual diagnosis in severe mental illness is an area of growing concern. The negative implications of either alcohol or non-alcohol substance use among patients with severe mental illness is an important area of focus. The aim of this study is to determine the prevalence of alcohol or non-alcohol substance use dual among patients with severe mental illness that is admitted to Hospital Mesra Bukit Padang. This study will also be looking at their demographic characteristics. In addition, this research attempts to study the possible association of clinical factors and outcomes from alcohol or non-alcohol substance use disorder dual diagnosis. This is a crosssectional study conducted in the inpatient ward of Hospital Mesra Bukit Padang. Patients who meet the inclusion and exclusion criteria are invited to participate in this study. Sociodemographic and clinical data were obtained from patients who consented based on questionnaire designed by the research team. Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM 5) was used to establish diagnosis of severe mental illness. Mini-International Neuropsychiatric Interview (M.I.N.I) was used to exclude other psychiatric disorders and to screen for alcohol or non-alcohol substance use disorder comorbidity. Outcomes and severity of different domains among severe mental illness patients was assessed with Addiction Severity Index (ASI).The association of demographic, clinical factors and outcomes of patients with dual diagnosis was examined. A total of 152 patients participated in this study. More than half, 51.3% ( n=78) of patients with severe mental illness had comorbid alcohol use disorder and, 29.6%( n= 45) with non-alcohol substance use disorder, predominantly amphetamine type stimulants. Majority of patients were male (61.2%), Kadazan (42.1%), single (52.6%), below tertiary iv level of education (52.6%) and unemployed (75%). Both univariate and multivariate analysis showed that gender, race and alcohol use disorder were associated factors between severe mental illness with co-morbid non-alcohol substance use disorder. Among patients with severe mental illness and alcohol use disorder, univariate analysis similarly showed that gender, race and non-alcohol substance use disorder were associated factors and when analyzed with multivariate analysis were still significantly associated. Associated clinical factors and outcomes via multivariate analysis also showed more number of hospitalizations among patients with severe mental illness and substance use disorder with severe addiction severity index scores based on legal, family and psychiatric status. Among patients with severe mental illness and alcohol use disorder, similarly had more number of hospitalizations and severe addiction severity index scores in domains of family and psychiatric status. Suicidality was higher among patients with severe mental illness with alcohol use disorder with equal odds among races. The prevalence of severe mental illness dual diagnosis was high in this study with poorer outcomes, higher rates of admissions and risk of suicidality. This highlights the importance of provisions for a more holistic treatment approach among patients with dual diagnosis.